Relevance Theory and Translation - Kliffer, Michael; Stroinska, Magda (Linguistica Atlantica, 2004)
Linguistic theory and translation theory both deal with language; however, they rarely meet or use each other's results in order to advance their individual areas of research. Linguists often seem to look at translation as either trade or art rather than science, and translators show cynicism about linguistic inquiry ignoring real language data. This paper focuses on one particular area of concern in both linguistics and translation: how to incorporate pragmatics into an explanation of which translation or interpretation is best for a given linguistic expression in a given linguistic and extra-linguistic context? Students in practical translation classes do not appreciate explanations along the lines "this is simply how you would say it in language X" or "this is what the speakers of X would say in this situation". Speakers of X are balancing their knowledge of rules and conventions of language use with pragmatic know-how; they are making choices that translators - both human and machine - are supposed to imitate in the target language context. We present several examples and discuss how Sperber and Wilson's Relevance Theory could claim translational explanatory adequacy in its handling of the "division of labour" between codal knowledge and inferencing.